2020
DOI: 10.3390/su12093802
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Life Expectancy in Romania between 1990 and 2018. A Territorial Analysis of Its Determinants

Abstract: The present study proposes a multiscale analysis of the dynamics of life expectancy at birth in Romania from 1990 to 2018, starting from the hypothesis of its dependence on the level of economic development or the quality of the public health infrastructure. Information from official sources (National Institute of Statistics (INS), Eurostat) was processed using agglomerative hierarchical clustering, principal component analysis and multiple regression. The main part of the analysis is devoted to the evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The patients undergoing rTKA procedures were on average 67.81 (± 8.02) years old at the moment of surgery; additionally, 15.79% of patients required second revision surgery, and 2.83% of patients required a third intervention. This raises concerns, especially when considering the mean age of the patients who require rTKA surgery and the rising average life expectancy in our country [ 61 , 62 ]. Given the increasing number of patients living longer, healthier, and more active lives, it is becoming increasingly apparent that a large number of individuals who underwent primary TKA procedures will eventually require revision surgery for their primary implant.…”
Section: Discussionmentioning
confidence: 99%
“…The patients undergoing rTKA procedures were on average 67.81 (± 8.02) years old at the moment of surgery; additionally, 15.79% of patients required second revision surgery, and 2.83% of patients required a third intervention. This raises concerns, especially when considering the mean age of the patients who require rTKA surgery and the rising average life expectancy in our country [ 61 , 62 ]. Given the increasing number of patients living longer, healthier, and more active lives, it is becoming increasingly apparent that a large number of individuals who underwent primary TKA procedures will eventually require revision surgery for their primary implant.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the presence of exceptional cases, which deviate from the main group, may raise discussion, as in the case of the Republic of Moldova or Hungary within the Eastern European countries. Romania’s position within the same group, close to Ukraine, at a significant distance from the more compact group of the other Eastern European countries, may also raise discussion, with some studies indicating a strong regional specificity at national level, closely linked to the level of development, the quality of health infrastructure or the particularities of the natural environment [ 57 ]. As the patterns of evolution of the causes of mortality at the global level have been highlighted, it can be concluded that they are the expression of distinct phases of the transition of public health systems, from a focus on prevention, typical of developed countries, to efforts to limit forms of morbidity considered to be a thing of the past but still common in developing countries.…”
Section: Discussionmentioning
confidence: 99%